Rancang Bangun Daily Pre-Trip Inspection (Rampcheck) Berbasis Web (Studi Kasus SBU Pemeliharaan Perum PPD) - Agustian , Dodi; Wardiana, Lolyta Prima; Kaharmen, Herman M. (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2018)
Daily Pre-Trip Inspection is an activity of checking vehicle (rampcheck) conducted before the vehicleoperate in highway. Perum PPD is one of the Public Company in the field of transport Jabodetabekarea. Many communities who are passionate about public transport, making the government increasesthe operational bus to Perum PPD 400 units in the year 2015. With the number of vehicles inoperation, also needed an efficient time on checking system. With the Daily Pre-Trip Inspection-basedwebsite as a new innovation in the checking system is expected to help the system of data collectionand storage of secure data quickly and accurately.In the process of the website using the R & D(Research and Development), which includes the analysis, design, development, implementation andevaluation using a MySQL database and PHP programming. The functionality of this website for theimportation, storage and report generation data checks the vehicle with 4 menu main menu; datainput, print the data, setting data and user profile settings.With a system of checks Daily Pre-TripInspection web-based, can facilitate the distribution of data and improve the effectiveness of time.